2020
DOI: 10.1186/s13075-020-02163-6
|View full text |Cite
|
Sign up to set email alerts
|

Sarilumab and adalimumab differential effects on bone remodelling and cardiovascular risk biomarkers, and predictions of treatment outcomes

Abstract: Background: Interleukin-6 (IL-6) is a pleiotropic cytokine that plays a key role in the pathogenesis of rheumatoid arthritis. Sarilumab is a human monoclonal antibody that binds membrane-bound and soluble IL-6 receptor-α to inhibit IL-6 signalling. The aim of this study was to compare the effects of sarilumab and adalimumab (a tumour necrosis factor alpha inhibitor) monotherapy on levels of circulating biomarkers associated with the acute-phase response, bone remodelling, atherothrombosis, anaemia of chronic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 24 publications
1
21
0
2
Order By: Relevance
“…In the ROC analysis, SAA was revealed to be moderately accurate (AUROC 0.7-0.9) in discriminating poor and high HRQoL as well as in assessing disease activity [ 27 ]. In line with our observation, it was reported that SAA correlates with HRQoL measures in systemic sclerosis and could be a predictor of patient-reported outcome response in patients with rheumatoid arthritis [ 28 , 29 ]. However, the HRQoL in patients with chronic diseases could be influenced by multiple factors such as disease severity and the use of medications such as glucocorticoids [ 30 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the ROC analysis, SAA was revealed to be moderately accurate (AUROC 0.7-0.9) in discriminating poor and high HRQoL as well as in assessing disease activity [ 27 ]. In line with our observation, it was reported that SAA correlates with HRQoL measures in systemic sclerosis and could be a predictor of patient-reported outcome response in patients with rheumatoid arthritis [ 28 , 29 ]. However, the HRQoL in patients with chronic diseases could be influenced by multiple factors such as disease severity and the use of medications such as glucocorticoids [ 30 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…Levels of soluble IL-6 receptor were not associated with differential response with sarilumab versus placebo or adalimumab (data not shown). Changes in other biomarkers that were assessed in these studies have been discussed previously (18,19).…”
Section: Discussionmentioning
confidence: 92%
“…Analyses were performed using continuous and categorical biomarker variables, with patients grouped into tertiles according to baseline IL-6 or CRP level (high, medium, or low) (Supplementary Table 1, available on the Arthritis & Rheumatology website at http://onlin elibr ary.wiley.com/doi/10.1002/art.41299/ abstract). Additional biomarkers were assessed in both studies (18,19).…”
Section: Methodsmentioning
confidence: 99%
“…An acute increase in Lp(a)-OxPL may then predispose to acute thrombotic events by tilting the balance of coagulation to a prothrombotic state by inhibiting natural fibrinolysis et al [40], the anti-TNFalpha antibody (adalimumab) did not affect Lp(a) levels, showing a specific effect to IL-6 on Lp(a) biology as opposed to a generalized proinflammatory effect [40]. In addition, sarilumab another anti-IL-6R mAb has been shown to lower Lp(a) by 41% compared with 2.8% for adalimumab [57]. Both tocilizumab and sarilumab have completed phase 2 trials in severe COVID-19 patients, and phase 3 trials are currently underway.…”
Section: The Role Of Il-6 In Plasma Lp(a) Levelsmentioning
confidence: 99%